Functional reconstitution and osmoregulatory properties of the ProU ABC transporter from Escherichia coli. (March 2013) - Gul, Nadia; Poolman, Bert
Abstract The ATP-binding cassette (ABC) transporter ProU from Escherichia coli translocates a wide range of compatible solutes and contributes to the regulation of cell volume, which is particularly important when the osmolality of the environment fluctuates. We have purified the components of ProU, i.e., the substrate-binding protein ProX, the nucleotide-binding protein ProV and the transmembrane protein ProW, and reconstituted the full transporter complex in liposomes. We engineered a lipid anchor to ProX for surface tethering of this protein to ProVW-containing proteoliposomes. We show that glycine betaine binds to ProX with high-affinity and is transported via ProXVW in an ATP-dependent manner. The activity ProU is salt and anionic lipid-dependent and mimics the ionic strength-gating of transport of the homologous OpuA system.